Intraspecific polymorphism of pollen grains in Artemisia herba Alba Asso in the Tiaret region (West of Algeria) - Maghni, Benchohra; Hammou, Mohammed Ait; Maghni, Anfal Bochra; Baghdache , Wahiba; Belkilali , Nebia; Khanfer , Imane (Future Science, 2025)
This study allowed us to determine the appearance and pollen apertures of 200 individuals of Atrémesia herba alba from three areas in Algeria. The pollen morphology determined at the three stations studied is Tricolorpé, of which two grain shapes were encountered, spherical and elongated with three aper-tures and distinct diameters. Results obtained from pollen di-ameter measurements revealed a significant effect, which con-firms a very marked intra- and inter-population variability of this character. Indeed, the spherical pollen diameters vary be-tween 13.20 and 20 µm (Ain Dheb area) and between 16.56 and 29.90 µm in individuals from the two Chellala areas. The elon-gated pollen diameters from the Chellala region have diameters fluctuating between 34.31/25.46 to 29.90/16.56 µm and have diameters between 19/14.81 and 28.55 /18.54 µm for the Ain Dheb area.